2002
DOI: 10.1053/euhj.2002.3400
|View full text |Cite
|
Sign up to set email alerts
|

The endothelial nitric oxide synthase (Glu298Asp and –786T>C) gene polymorphisms are associated with coronary in-stent restenosis

Abstract: In patients with coronary artery disease, the possession of the 298Asp and -786C variants of the eNOS gene are a risk factor for coronary in-stent restenosis, demonstrating the importance of the nitric oxide system in restenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 33 publications
3
39
0
1
Order By: Relevance
“…40 Furthermore, serum plasma activity of ACE is thought to play a major role in the development of restenosis after coronary stent implantation. 41,42 Recently, a number of articles in the literature reported on the relationship between ACE I/D polymorphisms and coronary restenosis risk [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] ; however, the results are inconsistent or even contradictory. This discrepancy may result from the small sample size, ethnic difference, false positive results, and/or study design in each study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…40 Furthermore, serum plasma activity of ACE is thought to play a major role in the development of restenosis after coronary stent implantation. 41,42 Recently, a number of articles in the literature reported on the relationship between ACE I/D polymorphisms and coronary restenosis risk [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] ; however, the results are inconsistent or even contradictory. This discrepancy may result from the small sample size, ethnic difference, false positive results, and/or study design in each study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that certain genetic polymorphisms are recognized to be associated with the risk of coronary restenosis. [14][15][16][17][18][19] Among these genes, the ACE gene polymorphisms were considered as a risk factor of coronary restenosis in several published papers [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] ; however, the results of these studies were inconsistent. Rebrova et al 34 found that ACE genetic polymorphism is associated with coronary restenosis risk.…”
Section: Association Of Ace Insertion or Deletion Polymorphisms With mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified genes associated with in-stent restenosis [14][15][16][17][18] . In this study, we report a novel finding for strong association of ALOX5AP SNPs and haplotypes with instent restenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (47) did observe a potential involvement of 786T3 C, Glu 298 Asp, and intron 8 single-nucleotide polymorphism (SNP) variants in the atherogenic process in diabetic subjects with CAD. Other studies showed that homozygosity of Glu 298 Asp and Ϫ786T3 C polymorphisms of the NOS3 gene represented an independent risk factor for in-stent restenosis (12,40), and the 894G3 T polymorphism of NOS3 gene was associated with an increased risk of death and/or myocardial infarction within 1 yr after stent placement (13).…”
mentioning
confidence: 99%